Application of The Concept of Welfare State in The Implementation of Health Social Security Programs - Mustainah; Arie, Marthen; Aspan, Zulkifli (Universitas Islam Negeri Alauddin Makassar, 2023)
Indonesia adopts the concept of a welfare state. However, there are many challenges, such as the sustainability of the national health insurance program, equal distribution of health facilities and subsidies for people who cannot afford it, so they have not achieved expectations. The Welfare State is an ideal idea of how the state carries out its duties in order to serve all citizens towards a harmonious and prosperous life order. The Indonesian state is one of the adherents of the concept of a material legal state which actually adopts the concepts of a welfare state which can be implicitly found in the general explanation of the 1945 Constitution of the Republic of Indonesia. However, there are many challenges such as the sustainability of the national health insurance program, equal distribution of health facilities and subsidies for people who cannot afford it so that it has not achieved what was expected.